Flaked corn, wheat, and sorghum grain for growing pigs - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred fifty-three barrows and gilts were used to evaluate flaking of corn, wheat, and sorghum grain for weaned pigs. Flaking increased rate of gain and improved feed efficiency (9 to 10%). Pigs fed corn rations gained significantly faster and were more efficient than pigs fed sorghum grain or\ wheat; and pigs fed sorghum grain gained faster and were more efficient than pigs fed wheat, regardless of processing method.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Flaked corn; Wheat; Sorghum grain; Growing pigs